Well-Known and Novel Adipokines as Metabolic Orchestrators: From Pathophysiological Insights to Therapeutic Perspectives - Şeker, Esma Nur; Afacan, Muhammed Yusuf; Kahraman, Selin; Yanar, Karolin; Aydın, Seval (Cerrahpaşa Medical Journal, 2025)
Adipokines are bioactive signaling proteins predominantly secreted by active metabolic and endocrine organ—white adipose tissue—and serve as metabolic orchestrators linking inflammation, appetite regulation, insulin sensitivity, energy metabolism, and cognitive function. Adipokines are categorized into 2 groups: well-known adipokines such as leptin, adiponectin, orexin, apelin, visfatin and novel adipokines including irisin, C1q tumor necrosis factor-related proteins, subfatin, isthmin, vaspin, etc. Novel adipokines are being identified day by day, resulting in a growing variety of adipokines. Adipokines that function at both local and systemic levels can have either pro-inflammatory or anti-inflammatory effects depending on their functionally diverse complex signaling pathways including Janus kinases/signal transducer and activator of transcription proteins, 5’-adenosine monophosphate-activated protein kinase (AMPK), phosphoinositide 3-kinase / protein kinase B, mitogen-activated protein kinase, and toll-like receptor 4. Disruption of systemic homeostasis triggers overproduction of adipokines and facilitates the development of pathological conditions and metabolic and cardiovascular, skeletal, neurodegenerative and eating diseases/disorders, such as obesity, insulin resistance, type 2 diabetes, cardiovascular diseases, osteoarthritis, multiple sclerosis, and Alzheimer’s disease. Comprehending the structures, mechanisms, and actions of adipokines is crucial for identifying potential therapeutic targets. Modulation of adipokine profiles through pharmacological interventions may represent a promising strategy for enhancing metabolic health. This comprehensive review highlights the fundamental roles of classical and novel adipokines in health and disease and advocates for further research into their diagnostic and therapeutic potential. Cite this article as: Şeker EN, Afacan MY, Kahraman S, Yanar K, Aydın S. Well-known and novel adipokines as metabolic orchestrators: from pathophysiological insights to therapeutic perspectives. Cerrahpaşa Med J. 2025, 49, 0098, doi: 10.5152/cjm.2025.25098.